PENGARUH ADISI RAGI TAPE (Saccharomyches cerevisae) TERHADAP UNSUR HARA NITROGEN DAN NILAI PH PUPUK ORGANIK PADAT FESES DOMBA LOKAL KEBUMEN: THE EFFECT OF ADDITION OF TAPE YEAST (Saccharomyches cerevisae) ON NITROGEN NUTRIENT ELEMENTS AND PH VALUE OF SOLID ORGANIC FERTILIZER FROM LOCAL SHEEP FECES FROM KEBUMEN - Althaf Muhammad El Hikam; Aqil Adyatama; Nunur Nuraeni (Tropical Animal Science, 2026)
Although sheep manure can be an environmental hazard, it is also a useful source of solid organic fertilizer. The purpose of this study was to determine the impact of various doses of tape yeast (Saccharomyces cerevisiae) on the pH value and total nitrogen (N) content of solid organic fertilizer made from local Kebumen sheep manure. This study included a total of four treatments, each replicated three times. Each of the four treatments consisted of the addition of one piece of tape yeast per fifteen kg of sheep manure in P1, two pieces in P2, three pieces in P3, and four pieces in P4. Fermentation took fourteen days to complete. Laboratory examination of total nitrogen content and pH value (measured using a pH meter) were among the factors examined. After initial testing with DMRT, data were analyzed using ANOVA. Results for the solid organic fertilizer showed a range of pH values ??from 7.10 to 7.17 and total N content from 2.240% to 2.429%. In terms of descriptive analysis, all treatments pH and total N levels were within the acceptable range for organic fertilizer (SNI). However, statistical analysis showed that neither the pH value nor the total N content of solid organic fertilizer made from sheep feces were significantly affected by various doses of tape yeast (P>0.05). The pH and nitrogen characteristics of the fertilizer were not affected by the addition of tape yeast up to a dose of 4 pieces per 15 kg of material. This indicates that the main raw material, sheep feces, is the most important factor in determining fertilizer quality. All procedures produced high-quality, ready-to-use solid organic fertilizer.